2022
DOI: 10.1177/1475472x221107375
|View full text |Cite
|
Sign up to set email alerts
|

Role of nozzle-exit boundary layer in producing jet noise

Abstract: Often the measurements from different jet noise studies, which are thought to have been acquired at or corrected to identical jet conditions, do not match when compared to each other. This study looks at the nozzle-exit boundary layer as a possible factor for these differences. The nozzle-exit boundary layer state can easily be changed depending on the design of the jet-facility or the nozzle. To this end, jet noise measurements and nozzle-exit velocity profile measurements were acquired for nozzles where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…It has been shown in a number of studies including by the current authors 13 that high-frequency jet noise reduces with thicker, more-developed nozzle-exit boundary layers. This indicates that if the boundary layer states of the jets compared in the any of the above studies were significantly different, the jet noise level differences observed could in-part be due to these differences.…”
Section: Introductionmentioning
confidence: 69%
“…It has been shown in a number of studies including by the current authors 13 that high-frequency jet noise reduces with thicker, more-developed nozzle-exit boundary layers. This indicates that if the boundary layer states of the jets compared in the any of the above studies were significantly different, the jet noise level differences observed could in-part be due to these differences.…”
Section: Introductionmentioning
confidence: 69%
“…An observation on nozzle size effect is made here based on the present and earlier results of. 5,45 The differences between the ASME design and the Conic cases are somewhat less pronounced with the 2 00 nozzles compared to the 1 00 nozzles in. 5 For example, in, 5 the transition to turbulence with the Conic nozzle around M J =0.3 was much sharper, and the difference in peak turbulence between the two cases was larger.…”
Section: Results For Conic and Asme Nozzlesmentioning
confidence: 99%
“…Relatively recently, a large number of numerical as well as a few experimental studies have been conducted on the initial BL effect as well as the effect of upstream conditions on flow and noise. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Most of the studies on initial BL effect were comprehensive also analyzing the flow field evolution and its stability characteristics but here we focus on the far field noise vis-à-vis the exit BL state and thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in agreement with experimental data presented in [12,13] where the noise emitted by tripped and un-tripped jets was investigated. Karon and Ahuja [14] found that a jet cexhausting from nozzles designed to reduce the axial velocity variation and the turbulence intensity, produces more noise compared to a nozzle with a fully developed flow at the exit. Furthermore, as speculated by Zaman [5], an increase of turbulence intensity in the initial region of the jet shear layer leads to an increase of highfrequency noise.…”
Section: Introductionmentioning
confidence: 99%